TERT promoter hotspot mutations and gene amplification in metaplastic breast cancer - da Silva, Edaise M. (NPJ Breast Cancer, 2021)
Metaplastic breast cancers (MBCs) are characterized by complex genomes, which seem to vary according to their histologic subtype. TERT promoter hotspot mutations and gene amplification are rare in common forms of breast cancer, but present in a subset of phyllodes tumors. Here, we sought to determine the frequency of genetic alterations affecting TERT in a cohort of 60 MBCs with distinct predominant metaplastic components (squamous, 23%; spindle, 27%; osseous, 8%; chondroid, 42%), and to compare the repertoire of genetic alterations of MBCs according to the presence of TERT promoter hotspot mutations or gene amplification. Forty-four MBCs were subjected to: whole-exome sequencing (WES; n = 27) or targeted sequencing of 341-468 cancer-related genes (n = 17); 16 MBCs were subjected to Sanger sequencing of the TERT promoter, TP53 and selected exons of PIK3CA, HRAS, and BRAF. TERT promoter hotspot mutations (n = 9) and TERT gene amplification (n = 1) were found in 10 of the 60 MBCs analyzed, respectively. These TERT alterations were less frequently found in MBCs with predominant chondroid differentiation than in other MBC subtypes (p = 0.01, Fisher’s exact test) and were mutually exclusive with TP53 mutations (p < 0.001, CoMEt). In addition, a comparative analysis of the MBCs subjected to WES or targeted cancer gene sequencing (n = 44) revealed that MBCs harboring TERT promoter hotspot mutations or gene amplification (n = 6) more frequently harbored PIK3CA than TERT wild-type MBCs (n = 38; p = 0.001; Fisher’s exact test). In conclusion, TERT somatic genetic alterations are found in a subset of TP53 wild-type MBCs with squamous/spindle differentiation, highlighting the genetic diversity of these cancers.